1997
DOI: 10.1016/s0954-6111(97)90089-5
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of muscle energy metabolism in patients with sleep apnoea syndrome

Abstract: Impairment of muscle energy metabolism has been demonstrated in normal subjects with chronic hypoxaemia (altitude chronic respiratory failure). The purpose of this study was to verify the hypothesis that a comparable condition could develop in patients with sleep apnoea syndrome (SAS), considering that they are exposed to prolonged and repeated hypoxaemia periods. Muscle metabolism was assessed in 11 patients with SAS performing a maximal effort on cycloergometer. In comparison with normal subjects, SAS patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
70
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(82 citation statements)
references
References 20 publications
11
70
0
1
Order By: Relevance
“…A reduced peak VO 2 in patients suffering from OSA has been observed in previous studies. 12,16,32 Our study confirmed not only a significantly lower peak VO 2 (in mL/kg/min), but also a lower percent predicted VO 2 in patients with OSA than in controls. The causes of reduced exercise capacity in patients with OSA remain unclear.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…A reduced peak VO 2 in patients suffering from OSA has been observed in previous studies. 12,16,32 Our study confirmed not only a significantly lower peak VO 2 (in mL/kg/min), but also a lower percent predicted VO 2 in patients with OSA than in controls. The causes of reduced exercise capacity in patients with OSA remain unclear.…”
Section: Discussionsupporting
confidence: 75%
“…Potential contributing factors include left and right ventricular diastolic dysfunction, 7,8 respiratory dysfunction, restrictive pulmonary disease, pulmonary hypertension, 14,15 and peripheral muscular abnormalities. 16 Our study population consisted of patients with OSA that were free of symptoms of cardiovascular disease, had a normal heart ultrasound, and had no ST-depressions in the ECG during exercise. Moreover, the similar values of oxygen pulse (VO 2 /heart rate) at peak exercise in patients with OSA and the control group, and the absence of hypoxemia during exercise in all patients were not consistentwith cardiac or pulmonary causes as explanations for the reduced exercise capacity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the positive, significant correlation between maximal power and mean SpO 2 during sleep, this significance did not hold after the partial correlation analysis with daytime PaO 2 as a control variable, unlike the close correlation found between VO 2 max and minimum SpO 2 during sleep in 12 patients with OSAS. (17) The desaturation found during maximal exercise in relation to rest was quite low (an average of 1%) compared to the much more significant desaturation during sleep, with a mean 9% drop in SpO 2 . It is estimated that cardiovascular stress during sleep can be, in some cases, even more intense than that reached during maximal exercise.…”
Section: Resultsmentioning
confidence: 87%
“…Some authors have found reduced exercise capacity in patients with OSAS, (12,13) although others have demonstrated no such impairment. (14,15) It is also known that increases in the levels of C-reactive protein (CRP), platelets, fibrinogen, and interleukin-6 are associated with nocturnal hypoxemia in patients with OSAS, (16) together with altered autonomic tone, (11) altered daytime catecholaminergic activity, (17) and increased diastolic blood pressure (DBP) during maximal exercise. (18) Our objective in this study was to evaluate the impact of nocturnal oxygen desaturation on maximal aerobic capacity and on its hemodynamic alteration components, as well as to determine maximal respiratory pressures, maximal voluntary isometric contraction (MVIC) force, and comparative CRP levels in patients with COPD, presenting normoxemia or mild hypoxemia during the day, with and without nocturnal oxygen desaturation.…”
Section: Introductionmentioning
confidence: 99%